Season of birth and subclinical psychosis: Systematic review and meta-analysis of new and existing data. Issue 3 (28th February 2015) - Córdova-Palomera, Aldo; Calati, Raffaella; Arias, Bárbara; Ibáñez, Manuel-Ignacio; Moya, Jorge; Ortet, Generós; Crespo-Facorro, Benedicto; Fañanás, Lourdes
Abstract: Season of birth (SOB) has been shown to modify the risk of several health outcomes, including a number of neuropsychiatric disorders. Empirical evidence indicates that subclinical forms of psychosis in the general population share some risk factors with categorical diagnoses of psychosis. Hence, by systematically reviewing and meta-analyzing new and existing data, the current work aimed to determine whether there is evidence of an association between winter SOB and subclinical psychosis in the general population. Our meta-analytic results do not indicate an association between winter SOB and schizotypy in adult populations, although they indicate winter SOB may be a risk factor for psychotic experiences or symptoms in children around 12–15 years (OR=1.12, 95%CI:1.03–1.21). In the whole new dataset for adults ( n =481, mean age=22.8 years) no association was detected in either an unadjusted model or adjusting for gender and age. Overall, our results indicate that the association between winter SOB and increased subclinical psychosis may hold in children, but does not in the broad general adult population. Nevertheless, the epidemiological and clinicopathological significance of winter SOB as a risk factor for subclinical psychosis would probably be slight due to the small effect sizes indicated by the reports available to date. Highlights: A systematic review and meta-analysis of season of birth and subclinical psychosis. Winter season of birth may not affect subclinical psychosis in healthy adults. Winter season of birth seems to increase risk of child subclinical psychosis. Effect size of winter season of birth on risk of subclinical psychosis is small.